Frontispiece: Table of Spectra - Schellen, Heinrich (Spectrum Analysis in its Application to Terrestrial Substances, and the Physical Constitution of the Heavenly Bodies, 1872)
Chromolithograph of a table of spectra in full color.
Keywords: Scientific illustration; Spectrum analysis